Archetyp „cienia” w strukturze powieści „Zbrodnia i kara” Fiodora Dostojewskiego - Jaworski, Mateusz (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The aim of the article is to show the interrelations between the works of Carl Gustav Jung and Fyodor Dostoyevsky with particular emphasis on the archetype of shadow. The aforementioned archetype has been analyzed and characterized in the paper in order to interpret the novel Crime and Punishment in the psychoanalytical key. This category has been analyzed at the level of the structure and plot of the work. Consequently, the author of the present article attempts to interpret the functions of the main characters of Crime and Punishment and divides them into triads related to relevant Jungian archetypes. The research amounts to an incentive to further explore the Jungian traces in the works of Fyodor Dostoyevsky.